Digital Business Discourse
XV, 274 p.
Keywords: This book provides a timely and comprehensive snapshot of the current digital communication practices of today's organisations and workplaces, covering a wide spectrum of communication technologies, such as email, instant messaging, message boards, Twitter, corporate blogs, consumer reviews and mobile communication technologies.